Analisa Pengaruh Tingkat Penerapan BIM 5D Terhadap Kinerja Waktu Proyek Konstruksi - Santoso, Imam Sugeng; Suroso, Agus; Amin, Mawardi (Journal of Industrial and Engineering System, 2023)
In construction, risks are usually requests for additional time, cost, or quality of work. Disputes will occur If risks are not resolved properly. In the industrial revolution 4.0, we can use the Building Information Modeling (BIM) method to increase efficiency. BIM is a digital display that contains all information about building elements integrated with the building's life cycle period. BIM will optimize the performance of construction projects. In Indonesia, several consultants/contractors have implemented BIM in construction projects. This study aims to determine and analyze what factors in the process of implementing BIM 5D that affect the performance of construction project time. The research method used is descriptive research method with the Q-method approach using closed survey research instruments to 53 contractor/consultant respondents using BIM. The results obtained from the 5D BIM indicators have 3 effects on the time performance of construction projects.